A DEADLY ENCOUNTER: LIGHTNING STRIKE ON A BOAT (Journal of Forensic Medicine & Toxicology, 2025)
Lightning strike is a rare and potentially fatal natural phenomenon. This case highlights a lightning strike on a boat where one person died while others survived, exploring conductive materials and injury outcomes.
Keywords: Lightning; Barotrauma; Keraunopathology